(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article contains the results of studies on the positioning of Ukraine in the international ratings of social-economic development. The presented analysis allows revealing the main components that have an impact on the state’s social policy. The obtained results allow forming directions of introduction of changes in the processes of regulation of social development of the country. An analysis of the criteria for socio-economic development of the country made it possible to identify the main international indicators. The Global Competitiveness Index of Ukraine includes 114 indicators, grouped in 12 categories: institutions, infrastructure, macroeconomic environment, health and primary education, higher education, product market efficiency, financial market development, technological readiness, market size, development level business, innovation. The World Competitiveness Index is set for 63 countries and is calculated on the basis of study of 50 criteria: 30 quantitative and 20 qualitative. The index of the prosperity of the countries, human development, human capital, social progress, and others correspond to the steps of the Maslow Pyramid, both in relation to the individual, and in relation to the social policy of the country. The results of the study allow us to conclude that the indicators of socio-economic development should be monitored according to the components of certain indices, as well as to identify the priority directions for which changes in the social policy to the state are necessary - activation of human development, healthcare reform, introduction of new technologies, ensuring the level of employment.